Direct Derivatization in Dried Blood Spots for Oxidized and Reduced Glutathione Quantification in Newborns - Isabel Ten-Doménech; Álvaro Solaz-García; Inmaculada Lara-Cantón; Alejandro Pinilla-Gonzalez; Anna Parra-Llorca; Máximo Vento; Guillermo Quintás; Julia Kuligowski (MDPI AG, 2022)
The glutathione (GSH)-to-glutathione disulfide (GSSG) ratio is an essential node contributing to intracellular redox status. GSH/GSSG determination in whole blood can be accomplished by liquid chromatography-mass spectrometry (LC-MS) after the derivatization of GSH with N-ethylmaleimide (NEM). While this is feasible in a laboratory environment, its application in the clinical scenario is cumbersome and therefore ranges reported in similar populations differ noticeably. In this work, an LC-MS procedure for the determination of GSH and GSSG in dried blood spot (DBS) samples based on direct in situ GSH derivatization with NEM of only 10 µL of blood was developed. This novel method was applied to 73 cord blood samples and 88 residual blood volumes from routine newborn screening performed at discharge from healthy term infants. Two clinical scenarios simulating conditions of sampling and storage relevant for routine clinical analysis and clinical trials were assessed. Levels of GSH-NEM and GSSG measured in DBS samples were comparable to those obtained by liquid blood samples. GSH-NEM and GSSG median values for cord blood samples were significantly lower than those for samples at discharge. However, the GSH-NEM-to-GSSG ratios were not statistically different between both groups. With DBS testing, the immediate manipulation of samples by clinical staff is reduced. We therefore expect that this method will pave the way in providing an accurate and more robust determination of the GSH/GSSG values and trends reported in clinical trials.